Proses Komunikasi Intrapersonal Dalam Pengambilan Keputusan Siswa-Siswi Untuk Mengikuti Pendidikan Di Sekolah Alkitab Batu - Palinggi, Tirza Veronica; Adi, Dodot Sapto; Saudah, Saudah (Yayasan Lentera Avanya Nagari, 2023)
One of the religious based educational institutions in Indonesia is Batu Bible School, where people who want to become Servants of God and want to join spiritual ministry can be trained and knowing more about Biblical Doctrine. The author found there were various intrapersonal communication experiences that experienced by the students. Students who have higher educational level and good career achievements before joining the Bible School, tend to go through a very intense intrapersonal communication process, with various inner situations. This is due to the cognitive dissonance or discomfort that arises because of differences in actions taken with thoughts that tend to lead to other actions. This research aims to understand about the intrapersonal communication process that occurs in decision making to take education in the Batu Bible School. The subjects of this study were students of the Batu Bible School in the 64-66 generation range, and who had previously worked but then decided to take education in the Bible School. This research is a qualitative descriptive research with the type of phenomenological approach. The result showed that the intrapersonal communication process in decision making is a very long process, unlimited, and impressed overlapping.